Uptake, distribution, and bioaccumulation of copper in the freshwater mussel Anodonta anatina - Nugroho, Andhika Puspito; Frank, Hartmut (Taylor & Francis, 2011)
Copper (Cu) is present in aquatic ecosystems in dissolved form, associated with suspended food particles, and as insoluble sulfide in the sediment. Due to its wide technical use and its presence in municipal and industrial waste waters, levels in rivers and sediments may be elevated. The aims of this study are to assess the relative importance of copper uptake by a typical freshwater mussel (Anodonta anatina), its distribution, accumulation among the mussel organs, and elimination. Using the stable isotope 63Cu as tracer, the mussels are exposed via the water (0.3 mmol L1 Cu) or via the food (1.5 mg L1 Cu-loaded algae, equivalent to 0.06 mmol L1 Cu) for 24 days. The levels of exogenous and total Cu increase in all body compartments. Relative increases are highest in the digestive gland, followed by mantle and gills. Upon depuration for 12 days, 63Cu is quickly but not completely eliminated.